Expression of DNA-damage response and repair genes after exposure to DNA-damaging agents in isogenic head and neck cells with altered radiosensitivity - Todorović, Vesna (Radiology and oncology (Ljubljana), 2022)
Background: Increased radioresistance due to previous irradiation or radiosensitivity due to human papilloma virus (HPV) infection can be observed in head and neck squamous cell carcinoma (HNSCC). The DNA-damage response of cells after exposure to DNA-damaging agents plays a crucial role in determining the fate of exposed cells. Tightly regulated and interconnected signaling networks are activated to detect, signal the presence of and repair the DNA damage. Novel therapies targeting the DNA-damage response are emerging; however, an improved understanding of the complex signaling networks involved in tumor radioresistance and radiosensitivity is needed. Materials and methods: In this study, we exposed isogenic human HNSCC cell lines with altered radiosensitivity to DNA-damaging agents: radiation, cisplatin and bleomycin. We investigated transcriptional alterations in the DNA-damage response by using a pathway-focused panel and reverse-transcription quantitative PCR. Results: In general, the isogenic cell lines with altered radiosensitivity significantly differed from one another in the expression of genes involved in the DNA-damage response. The radiosensitive (HPV-positive) cells showed overall decreases in the expression levels of the studied genes. In parental cells, upregulation of DNA-damage signaling and repair genes was observed following exposure to DNA-damaging agents, especially radiation. In contrast, radioresistant cells exhibited a distinct pattern of gene downregulation after exposure to cisplatin, whereas the levels in parental cells were unchanged. Exposure of radioresistant cells to bleomycin did not significantly affect the expression of DNA-damage signaling and repair genes. Conclusions: Our analysis identified several possible targets: NBN, XRCC3, ATR, GADD45A and XPA. These putative targets should be studied and potentially exploited for sensibilization to ionizing radiation and/or cisplatin in HNSCC. The use of predesigned panels of DNA-damage signaling and repair genes proved to offer a convenient and quick approach to identify possible therapeutic targets.
Keywords: DNA-damaging agents; gene expression; head and neck cancer; izražanje genov; ploščatocelični rak; poškodbe DNK; rak glave in vratu; squamous cell carcinoma